2017
DOI: 10.1590/0001-3765201720160662
|View full text |Cite
|
Sign up to set email alerts
|

Forage potential of native ecotypes of Paspalum notatum and P. guenoarum

Abstract: The Paspalum genus includes several species that are important for livestock in Rio Grande do Sul, such as P. notatum and P. guenoarum, typical of native pastures of the Pampa biome. The aim of this study was to investigate forage production and chemical composition of four ecotypes of these species in relation to the cv. 'Pensacola' (P. notatum). Ecotypes of P. guenoarum (Azulão and Baio) and P. notatum (André da Rocha and Bagual) and the cv. 'Pensacola' were evaluated for two years, during which four cuts/ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 7 publications
1
23
0
3
Order By: Relevance
“…The four hybrids (1020133, 102069, 103084, and 103061) exhibited good forage performance in different edaphoclimatic conditions (Saraiva, 2015). Ecotype Azulão is native to the subtropical and temperate regions of southern Brazil, Argentina, and Paraguay (Steiner et al., 2017), and showed good forage performance in subtropical conditions (Pereira et al., 2012). Aruana is a perennial grass used in intensive beef production systems in Brazil (Fernandes et al., 2014).…”
Section: Methodsmentioning
confidence: 99%
“…The four hybrids (1020133, 102069, 103084, and 103061) exhibited good forage performance in different edaphoclimatic conditions (Saraiva, 2015). Ecotype Azulão is native to the subtropical and temperate regions of southern Brazil, Argentina, and Paraguay (Steiner et al., 2017), and showed good forage performance in subtropical conditions (Pereira et al., 2012). Aruana is a perennial grass used in intensive beef production systems in Brazil (Fernandes et al., 2014).…”
Section: Methodsmentioning
confidence: 99%
“…In southern Brazil, these species predominate in the physiognomy and are critical for livestock production in the natural fields of the Pampa Biome. Studies have demonstrated the forage potential of different Paspalum species (Pereira et al, 2012;Motta et al, 2017;Steiner et al, 2017). Among Paspalum species, P. notatum Flüggeis salient, with native genotypes of recognized forage potential, which surpasses that of the commercial cultivar Pensacola predominantly used in the southern region of the country (Fachinetto et al, 2012, Weiler et al, 2018.Knowledge of the productive potential of promising genotypes released as new cultivars coupled with the appropriate use of input technologies can be used to intensify livestock production systems.…”
Section: Introductionmentioning
confidence: 99%
“…The CP content is an important trait for the selection and improvement of nutritional characteristics in forage plants. Steiner et al (2017) described mean values of 14.7% and 14.2% for CP content from "Azulão" and "Baio", respectively. The findings in this research revealed that there were hybrids with higher CP content than the ecotypes used as parents and the commercial cultivar, especially hybrid 102069 that had superior CP content in all harvests and years.…”
Section: Resultsmentioning
confidence: 98%
“…The selection of genotypes with greater forage production, forage quality and wide adaptability to diverse environments is one of the main goals in forage breeding programs. Steiner et al (2017) obtained higher forage production with two native ecotypes of P. guenoarum and two ecotypes of P. notatum compared to the cultivar "Pensacola" (P. notatum) which demonstrates the possibility to use native ecotypes as cultivated pastures. Forage quality may not be considered as important as biomass production in many forage systems.…”
Section: Introductionmentioning
confidence: 82%